Chemosensory of hemp seed oil extracted with hemp seed(Cannabis sativa L.) roasted under various conditions using electronic sensors and GC–MS/Olfactometry - Hyangyeon Jeong; Sojeong Yoon; Seong Min Jo; Seong Jun Hong; Younglan Ban; Hyeonjin Park; Moon Yeon Youn; Eui-Cheol Shin (Food Chemistry: X, 2024)
This study analyzed the flavor of six types of hemp seed oil (HSO) extracted with roasted hemp seed (RHS) under various conditions (Raw, 140 °C_9 min, 140 °C_12 min, 160 °C_12 min, 180 °C_6 min). Electronic tongue (E-tongue), electronic nose (E-nose), GC–MS (gas chromatography–mass spectrometry), and GC-O (gas chromatography–olfactometry) were used for HSO flavor analysis. As a result of the E-tongue analysis, the sweetness tends to increase in most samples as roasting. A total of 89 and 77 volatile compounds were detected through E-nose and GC–MS, and the main volatile compounds were identified as Maillard reaction products. A total of 16 odor active compounds were detected in the GC-O analysis, and in the case of 160 ℃_12 min and 180 ℃_6 min, the scent of Roasted hemp seed oil was more dominant than other aroma profiles. The results of this study are basic data on the flavor characteristics of HSO.